2021
DOI: 10.35371/aoem.2021.33.e6
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease in a worker exposed to insecticides at a greenhouse

Abstract: Background: Parkinson's disease (PD) is a rare, neurodegenerative disease with various occupational and environmental risk factors. Exposure to specific pesticides contributes significantly to the incidence of PD. However, it is difficult to measure the level of pesticide exposure in workers. This study presents the first case recognized the work-relatedness between PD and pesticide exposure. Case presentation: A 68-year-old male was diagnosed with PD after working with pesticides at a tomato greenhouse for 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A recent epidemiologic study by Kim et al [ 47 ] showed the relation between exposure to insecticides at a tomato greenhouse and PD. In this study, they considered a proven case of occupational PD for the first time, rebuilding his family and occupational history and reporting the illness.…”
Section: The Impact Of Food Contamination On the Onset Of Parkinson’s...mentioning
confidence: 99%
“…A recent epidemiologic study by Kim et al [ 47 ] showed the relation between exposure to insecticides at a tomato greenhouse and PD. In this study, they considered a proven case of occupational PD for the first time, rebuilding his family and occupational history and reporting the illness.…”
Section: The Impact Of Food Contamination On the Onset Of Parkinson’s...mentioning
confidence: 99%